New Business Opportunities in the Gen Z era - Safitri, Rahmalia (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
The 2024 election in Indonesia is attracting attention because generation Z is predicted to be the largest voter. They are known to be open to innovation, and active in technology, but also face challenges in decision-making and the need for valid information. Research using literature review and statistical analysis methods shows that the greatest influence on generation Z comes from individual development, social engagement, and social media. Social and technological changes shape generation Z as individuals who care about the environment, are critical, and are open to new experiences. SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats. Despite having strengths such as technological skills, generation Z also has weaknesses such as emotional instability. There are business opportunities in the fields of sports, eco-tourism, electronic services and creative arts, but you need to be alert to threats such as the tendency to be withdrawn and critical. By understanding these factors, businesses can adapt their products and services to capitalize on the potential of the generation Z market.